2021
DOI: 10.1001/jamainternmed.2020.7090
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mindfulness Meditation vs Headache Education for Adults With Migraine

Abstract: IMPORTANCE Migraine is the second leading cause of disability worldwide. Most patients with migraine discontinue medications due to inefficacy or adverse effects. Mindfulness-based stress reduction (MBSR) may provide benefit. OBJECTIVE To determine if MBSR improves migraine outcomes and affective/cognitive processes compared with headache education. DESIGN, SETTING, AND PARTICIPANTSThis randomized clinical trial of MBSR vs headache education included 89 adults who experienced between 4 and 20 migraine days per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(182 citation statements)
references
References 92 publications
3
142
2
1
Order By: Relevance
“…Migraine is characterized by attacks of throbbing, often unilateral, severe and pulsating headache, and associated with symptoms such as phonophobia, photophobia, vomiting, nausea, and cutaneous allodynia. [1][2][3] As the second leading cause of disability worldwide, 4,5 migraine significantly contribute to individual and societal burdens due to severe pain and environmental sensitivities. [6][7][8] Epidemiological studies have shown a higher prevalence of migraine in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Migraine is characterized by attacks of throbbing, often unilateral, severe and pulsating headache, and associated with symptoms such as phonophobia, photophobia, vomiting, nausea, and cutaneous allodynia. [1][2][3] As the second leading cause of disability worldwide, 4,5 migraine significantly contribute to individual and societal burdens due to severe pain and environmental sensitivities. [6][7][8] Epidemiological studies have shown a higher prevalence of migraine in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…These findings show that an ensemble of symptoms relating to experimentally evoked pain is targeted by mind-body therapy. Due to the ensemble's relationship with evoked pain, it could serve as a potential endpoint for clinical trials assessing treatments that modify evoked pain, as is the case with MBSR [42]. The present study is not without its limitations.…”
Section: Discussionmentioning
confidence: 94%
“…As reflected by recent expert international consensus 44 and systematic reviews, 45,46 clinical trials should always include outcomes that reflect the full impact of migraine on patient lives through assessing both disability and quality of life. Both disability and quality of life are worthy of being a primary outcome, including for pharmacological treatments as well as for implementation science and nonpharmacological treatment approaches 20,44,47 …”
Section: Discussionmentioning
confidence: 99%
“…Of note, the emotional health codes were represented more commonly in those who had participated in MBSR compared with HA Education. This is particularly interesting given that our quantitative RCT results demonstrated that MBSR improved multiple measures of well‐being more than HA Education (depression scores, quality of life, headache‐related disability, self‐efficacy, pain catastrophizing) 20 . However, mindfulness teaches individuals to pay attention to the present moment in a way that may increase their awareness of how migraine impacts quality of life, while minimizing the associated emotional reactivity.…”
Section: Strengths and Limitationsmentioning
confidence: 92%
See 1 more Smart Citation